LH

Chứng tỏ đa thức sau không có nghiệm:x^2+x+2

H24
19 tháng 4 2020 lúc 8:51

\(x^2+x+2=x^2+2.x+1+1-x=x^2+2.x.1+1^2+1-x\)

\(=\left(x+1\right)^2+1-x\)

Mk chỉ lm đc vậy thôi

Bình luận (0)
 Khách vãng lai đã xóa
NN
19 tháng 4 2020 lúc 9:22

\(x^2+x+2=x^2+2.\frac{1}{2}.x+\frac{1}{4}+\frac{7}{4}\)

\(=\left(x^2+2.\frac{1}{2}.x+\frac{1}{4}\right)+\frac{7}{4}=\left(x+\frac{1}{2}\right)^2+\frac{7}{4}\)

Vì \(\left(x+\frac{1}{2}\right)^2\ge0\forall x\)\(\Rightarrow\left(x+\frac{1}{2}\right)^2+\frac{7}{4}\ge\frac{7}{4}>0\)

\(\Rightarrow\)Đa thức đã cho vô nghiệm ( đpcm )

Bình luận (0)
 Khách vãng lai đã xóa